2017
DOI: 10.1128/aem.00966-17
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial and Fungal Communities Show Distinct Recovery Patterns during Forest Ecosystem Restoration

Abstract: Bacteria and fungi are important mediators of biogeochemical processes and play essential roles in the establishment of plant communities, which makes knowledge about their recovery after extreme disturbances valuable for understanding ecosystem development. However, broad ecological differences between bacterial and fungal organisms, such as growth rates, stress tolerance, and substrate utilization, suggest they could follow distinct trajectories and show contrasting dynamics during recovery. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
115
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(145 citation statements)
references
References 89 publications
26
115
1
3
Order By: Relevance
“…In contrast to bacteria, fungi have been known to be strongly reduced in abundance and richness following the physical destruction of the soil structure and hyphal networks that may require a longer time to re‐establish and recover in abundance (Hartmann et al., ; Lauber et al., ; Oehl et al., ; Rousk & Bååth, ; Sun, Li, Avera, Strahm, & Badgley, ; van der Wal et al., ; Verbruggen et al., ). Furthermore, soil tilling is well known to alter the abiotic properties of the soil and in our system it was observed that tilling increased soil pH and reduced soil silt content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to bacteria, fungi have been known to be strongly reduced in abundance and richness following the physical destruction of the soil structure and hyphal networks that may require a longer time to re‐establish and recover in abundance (Hartmann et al., ; Lauber et al., ; Oehl et al., ; Rousk & Bååth, ; Sun, Li, Avera, Strahm, & Badgley, ; van der Wal et al., ; Verbruggen et al., ). Furthermore, soil tilling is well known to alter the abiotic properties of the soil and in our system it was observed that tilling increased soil pH and reduced soil silt content.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the many past studies that have observed that soil tilling reduces soil fungal abundance and richness (Hartmann et al., ; Oehl et al., ; van der Wal et al., ; Verbruggen et al., ). Considering the physical destruction of fungal hyphae by tilling, the instability in the fungal abundance likely results from fungi requiring longer periods of time to re‐establish hyphal networks post disturbance (Rousk & Bååth, ; Sun et al., ). The slow development in fungal abundance post disturbance is also evidenced in our system where the tilling reduced fungal abundance throughout the growing season that only seemed to recover towards the end of the year, 6–7 months post tilling.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing reads associated with the skin fungal communities were processed as in Sun et al (2017). Sequences were quality filtered and processed using the USEARCH pipeline (Edgar, 2010).…”
Section: Sample Collectionmentioning
confidence: 99%
“…The phyla Proteobacteria, Actinobacteria and Acidobacteria were the most abundant, which support the findings reported in previous studies of forest soils (Deveau et al ., ; Sun et al ., ). These phyla seem to be abundant in most soils (Lauber et al ., ), which appears to indicate their functional importance (Lladó et al ., ).…”
Section: Discussionmentioning
confidence: 99%